Optimization of multiple enzymes production by fermentation using lipid-producing Bacillus sp. - Shrestha, Sarita; Chio, Chonlong; Khatiwada, Janak Raj; Kognou, Aristide Laurel Mokale; Qin, Wensheng (Frontiers in Microbiology, 2022)
The present study identified the pectinase-producing bacterium isolated from the contaminated broth as Bacillus sp. on 16S rDNA sequence analysis. The bacterium illustrated water-like droplets on the colony grown on the Sabouraud dextrose agar plate. It also exhibited multi-enzymes activities, such as pectinase, polygalacturonase, xylanase, and cellulase by using various agro-wastes as low-cost substrates. The orange peel was observed to be the best substrate among the agro-wastes used for maximum multi-enzymes (pectinase, polygalacturonase, xylanase, and cellulase). However, the bacterium demonstrated its capability to produce different enzymes according to the different substrates/agro-wastes used. The Plackett-Burman design was used to determine the essential influencing factors, while the Box Behnken design response surface methodology was for optimizing cultural conditions. At their optimal conditions (40℃ incubation temperature, 24 hours of incubation period, 1% w/v orange peel, and 2% v/v inoculum volume), the bacterium exhibited the maximum pectinase (9.49±1.25 U/mL) and xylanase (16.27±0.52 U/mL) activities. Furthermore, the study explored the ability of the bacterium to produce bacterial lipids and observed about 25% bacterial lipid content on a dry weight basis. Therefore, the bacterium is a good candidate for producing important multi-enzymes and subsequent agro-waste degradation controlling the environment, and facilitating waste management. Also, the bacterium can be a potential feedstock in producing renewable biofuel.